Configuration of Alternative Food Networks in western Mexico - Rodríguez Guerrero, Rodrigo; Orozco Hernández, Roberto Paulo; Leal Martínez, Gregorio; Eufracio Jaramillo, Jorge Federico; Alvarado Castro, Eric Rosalío (Cooperativismo & Desarrollo, 2023)
Introduction. The appearance and spread of COVID-19 have added to previous crises, revealing latent risks related to food. The Alternative Food Networks formed by groups oriented to the production, distribution, and consumption of food, have represented a possibility of access to healthy, ecologically sustainable food and with more socially just practices. The growth of these networks has been exponential in recent decades and the health emergency has led them to reconfigure rapidly; a process that will be addressed, in this article, for Western Mexico. Method. With a quantitative and qualitative approach, 96 experiences distributed in four states of the country are explored: Colima, Jalisco, Michoacán, and Nayarit. Results. It starts with the categorization of the networks and their analysis, answering two main questions: what are the organizational guidelines of these groups in Western Mexico? How were these guidelines reconfigured during the health emergency? Conclusions. A series of mechanisms that had been operating prior to the pandemic have favored the spatial and temporal redefinition of the organizations that integrate Alternative Food Networks, based on common principles of food sovereignty, agroecology, and solidarity economy.
Keywords: COVID-19; agroecology; food sovoreignty; solidarity economy; alternative food networks